Concurrent and cross-season protection of inactivated influenza vaccine against A(H1N1)pdm09 illness among young children: 2012–2013 case–control evaluation of influenza vaccine effectiveness. Issue 25 (9th June 2015) - Fu, Chuanxi; Xu, Jianxiong; Lin, Jinyan; Wang, Ming; Li, Kuibiao; Ge, Jing; Thompson, Mark G.
Highlights: We estimated VE of trivalent inactivated influenza vaccines (IIV3) against A(H1N1)pdm09 illness. VE of 67% (95% confidence interval = 58–74%) was observed for children less than age 9 years old. Fully vaccinated children under age 3 years old had higher VE than partially vaccinated children. We observed significant cross-season VE for IIV3 received up to two seasons earlier. Abstract: In 2012–2013, we examined 1729 laboratory-confirmed A(H1N1)pdm09 influenza cases matched 1:1 with healthy controls and estimated influenza vaccine effectiveness (VE) for trivalent inactivated influenza vaccine (IIV3) to be 67% (95% confidence interval = 58–74%) for ages 8 months to 6 years old. Among children aged 8–35 months old, VE for fully vaccinated children (73%, 60–81%) was significantly higher than VE for partially vaccinated children (55%, 33–70%). Significant cross-season protection from prior IIV3 was noted, including VE of 31% (8–48%) from IIV3 received in 2010–2011 against influenza illness in 2012––2013 without subsequent boosting doses.